Trajectories of Offending: Comparing US Born and Non-US Born Respondents in the Add Health - Watts, Stephen J. (American journal of criminal justice, 2023)
Immigration is sometimes associated with crime and delinquency in the mind of the public, and it is often assumed that individuals not born in the U.S. engage in more crime and delinquency than do the native born. However, not enough research to date has looked at offending across the life-course and compared trajectories between U.S. born and non-U.S. born populations. Guided by life-course perspectives and utilizing group-based trajectory modeling (GBTM), this article uses four waves of National Longitudinal Study of Adolescent to Adult Health (Add Health) data to describe and contrast longitudinal variations in offending behavior between US born and non-US born individuals. The analyses show that there are fewer offending trajectory groups among the non-U.S. born, and that they generally offend at lower levels across the life-course than do the U.S. born. Further analysis also shows differences between the two groups in factors that shape trajectory group membership.